Sources and space–time distribution of the electromagnetic pulses in experiments on inertial confinement fusion and laser–plasma acceleration. (7th December 2020) - Consoli, F.; Andreoli, P. L.; Cipriani, M.; Cristofari, G.; De Angelis, R.; Di Giorgio, G.; Duvillaret, L.; Krása, J.; Neely, D.; Salvadori, M.; Scisciò, M.; Smith, R. A.; et al.
Abstract : When high-energy and high-power lasers interact with matter, a significant part of the incoming laser energy is transformed into transient electromagnetic pulses (EMPs) in the range of radiofrequencies and microwaves. These fields can reach high intensities and can potentially represent a significative danger for the electronic devices placed near the interaction point. Thus, the comprehension of the origin of these electromagnetic fields and of their distribution is of primary importance for the safe operation of high-power and high-energy laser facilities, but also for the possible use of these high fields in several promising applications. A recognized main source of EMPs is the target positive charging caused by the fast-electron emission due to laser–plasma interactions. The fast charging induces high neutralization currents from the conductive walls of the vacuum chamber through the target holder. However, other mechanisms related to the laser–target interaction are also capable of generating intense electromagnetic fields. Several possible sources of EMPs are discussed here and compared for high-energy and high-intensity laser–matter interactions, typical for inertial confinement fusion and laser–plasma acceleration. The possible effects on the electromagnetic field distribution within the experimental chamber, due to particle beams and plasma emitted from the target, are also described. This article is part of a discussion meeting issue 'Prospects for high gain inertial fusion energy (part 2)'.